Sustainable Solvent Extraction Process for Fe Analysis in Radioactive Samples Based on Microfluidic Tools. Issue 2 (23rd February 2020) - Rassou, Somasoudrame; Vercouter, Thomas; Mariet, Clarisse
ABSTRACT: The decommissioning and dismantling of nuclear plants and the subsequent management of the wastes require a large number of radiochemical analyses in the timeline of the operations. Validated analytical methods for radionuclides measurements are employed to ensure reliable sample characterizations. The radioactivity of the samples, which induces handling and shipment constraints, and the use of harmful chemical reactants in some analytical procedures, are among the motivations to use miniaturized techniques that would considerably lower the amounts of samples and chemicals. Moreover the decrease of the analytical time is a major concern considering the increasing demand for radiochemical analyses. The purpose of this work is to develop a microsystem-based protocol for the recovery of 55 Fe from samples. Analytical solvent extraction protocols adapted to co-flow glass microsystems, were developed and tested on iron extraction into ethyl acetate. A first extraction protocol consists of the partitioning of the Fe(cupferrate)3 chelate, from the aqueous phase to the organic phase. A second extraction protocol is based on the reactive transfer of iron using the cupferron in the organic phase. The two protocols were tested on a single Y-junction and a double stage Y-junction glass microsystems. After optimization of the liquid flow rates, the iron extraction was achieved within about 2 s or less. While the best extraction yield of (60.3 ± 4.9) % was obtained with the former protocol in the double stage Y-junction, higher values of (83.1 ± 5.2) % and (81.7 ± 2.0) % were obtained with the single and double stage microsystems, respectively, with the second protocol. These last results compare well with the yield of (93.0 ± 2.3) % measured in batch and could even be optimized by using slightly longer microchannels. Such microsystem-based extractions will be further applied to the analysis of 55 Fe by liquid scintillation.